ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON THE LEVEL OF STUDENT SATISFACTION - Nurul Qomariyah; Siti Maysaroh (Faculty of Islamic Economics and Business, 2020)
Introduction: This study aims to determine whether there is an effect of service quality on student satisfaction at the Faculty of Economics and Business, Ahmad Dahlan University Yogyakarta. And to find out how the influence of the quality of Administration services, library services and parking services on student satisfaction. Methods: This research is a survey research using a questionnaire as the instrument. The population in this study were students of the Ahmad Dahlan University Faculty of Economics and Business Yogyakarta. The sample in this study were 121 active students of the Faculty of Economics and Business, Universitas Ahmad Dahlan Yogyakarta using the Porposive Sampling Method. Namely the technique of determining the sample for certain considerations. Test the validity of the instrument using Confir Motory Factor Analysis. While the reliability test used Alpha Crombach. The analysis technique used is multiple linear regression analysis technique. Results: The results of this study indicate that the Administration variable (X1) has a significant positive effect on student satisfaction at the Ahmad Dahlan University Faculty of Economics and Business Yogyakarta. While the library variable (X2) has a significant positive effect on student satisfaction at the Faculty of Economics and Business, Ahmad Dahlan University Yogyakarta. And the third variable is the Parking variable (X3) has a positive significant effect on student satisfaction at the Faculty of Economics and Business, Ahmad Dahlan University Yogyakarta. Keywords: Administration service quality, library service quality, parking service quality and student satisfaction.